Horizontally Differentiated Store Brands: Production Outsourcing to National Brand Manufacturers - Shun Shindo; Nobuo Matsubayashi (Journal of Applied Mathematics)
We study a retailer's strategic decision with regard to outsourcing the production of such types of store brands (SBs) to national brand (NB) manufacturers. The wholesale price of NB is assumed to be set by the manufacturer, while that of the SB is assumed to be set by the retailer. When a retailer outsources SB production to an NB manufacturer, the NB manufacturer might suffer from cannibalization due to offering both the SB and the NB, implying that a strategic interaction between the retailer and manufacturer is an important issue. Based on this motivation, we mainly focus on the strategy of a dominant retailer in such a situation and investigate it with a game-theoretic approach. We show that the optimal strategy for the SB retailer sensitively depends on the degree of differentiation between the SB and the NB. In particular, if both products are less differentiated, the retailer benefits from offering only the SB, and, in this case, the retailer should offer its wholesale price, after the manufacturer sets the NB wholesale price. Furthermore, it is shown that the optimal strategies of the retailer are socially efficient, if and only if the SB and the NB are sufficiently differentiated.